SPECIFIC FEATURES OF SPRING FLOOD FORMATION IN THE ARPA RIVER BASIN - Varduhi G. Margaryan; Ekaterina V. Gaidukova; Levon V. Azizyan; Amalya E. Misakyan (Водное хозяйство России: проблемы, технологии, управление)
The article considers main physical and geographical factors affecting the runoff, spring flood of rivers in the Arpa River basin, and analyzes the regularities of their spacetime distribution. The authors have obtained correlation relationship between the values of the flood runoff layer, the mean module maximum runoff and weighted average height of the catchment area of the Arpa River, between the mean annual maximum runoff module for the period floods and catchment areas of rivers. These dependencies can be used for preliminary estimates of the spring flood runoff of unexplored rivers of the territory under consideration. A close correlation between the values of the annual runoff and the runoff of the spring flood in the section of the Arpa River – Dzhermuk has been also revealed. It can be used for forecasting the annual flow.